2017
DOI: 10.15389/agrobiology.2017.3.622eng
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols of Red Grapes in Wine and Concentrates for Use in Rehabilitation Technologies

Abstract: A b s t r a c tIn recent years, as cardiovascular mortality is increasing, the interest in studying the influence of polyphenol-rich grape products (PRGP) on cardiovascular risks is constantly growing. The estimation of a safe and effective dose of PRGP deserves special attention, because an excessive consumption can lead to endothelial dysfunction and oxidative stress. The hygienic and curative properties the young branches of grapevine, leaves, berries, juice and wine are used in traditional medicine for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In the same line with our findings, other systematic reviews and meta-analyses confirmed the beneficial effects of GPCP on the obesity-induced chronic inflammation [ 120 ], lipid profile [ 121 ], blood glucose [ 87 ], systolic blood pressure, heart rate [ 57 , 122 ], endothelial function [ 56 ], liver and heart functions [ 87 ], metabolic syndrome, and type 2 diabetes [ 120 ]. In addition, the significant impact of GPCP was reported on oxidative stress in patients with Type 2 diabetes [ 23 , 44 ], pre hypertension [ 1 , 123 ], overweight [ 39 ], acute lymphoblastic leukemia [ 41 ], CVD [ 100 , 124 ], systemic sclerosis [ 96 ], Chronic Obstructive Pulmonary Disease [ 32 ], hemodialysis patient [ 46 , 125 , 126 ], hyperlipidemia [ 127 ], smoker [ 128 ], and healthy subjects [ 21 , 26 , 40 , 42 , 90 , 92 , 94 , 101 , 102 , 105 , 114 , 115 , 118 ]. In contrast with our results, some RCTs [ 36 , 38 , 43 , 95 , 104 , 106 , 116 , 119 , 129 ] reported no significant effect of GPCP on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line with our findings, other systematic reviews and meta-analyses confirmed the beneficial effects of GPCP on the obesity-induced chronic inflammation [ 120 ], lipid profile [ 121 ], blood glucose [ 87 ], systolic blood pressure, heart rate [ 57 , 122 ], endothelial function [ 56 ], liver and heart functions [ 87 ], metabolic syndrome, and type 2 diabetes [ 120 ]. In addition, the significant impact of GPCP was reported on oxidative stress in patients with Type 2 diabetes [ 23 , 44 ], pre hypertension [ 1 , 123 ], overweight [ 39 ], acute lymphoblastic leukemia [ 41 ], CVD [ 100 , 124 ], systemic sclerosis [ 96 ], Chronic Obstructive Pulmonary Disease [ 32 ], hemodialysis patient [ 46 , 125 , 126 ], hyperlipidemia [ 127 ], smoker [ 128 ], and healthy subjects [ 21 , 26 , 40 , 42 , 90 , 92 , 94 , 101 , 102 , 105 , 114 , 115 , 118 ]. In contrast with our results, some RCTs [ 36 , 38 , 43 , 95 , 104 , 106 , 116 , 119 , 129 ] reported no significant effect of GPCP on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of patients were formed: a group of patients with coronary heart disease (96 people) and a group of patients with hypertension (163 people). The research protocol was approved by the local Ethics Committee [42][43][44]. All patients received identical treatment as prescribed by the doctors of the institution.…”
Section: The Clinical Testing Of Products Rich In Grape Polyphenols Amentioning
confidence: 99%
“…Wine is rich in valuable compounds, such as polyphenols and vitamins, that can benefit human health [1][2][3]. Red wine polyphenols in particular exhibit anti-inflammatory, cardioprotective, antiallergic and antitumor effects [1,4]. Drinking wine as an aperitif stimulates gastric secretion and improves digestion [5].…”
Section: Introductionmentioning
confidence: 99%